A182 INFLAMMATORY BOWEL DISEASE AMONG SENIORS IN SASKATCHEWAN. (4th March 2021) - Shahmoradi, A; Fowler, S; Peña-Sánchez, J
Abstract: Background: Inflammatory bowel disease (IBD) is a chronic inflammatory condition comprised of two major disorders: ulcerative colitis (UC) and Crohn's disease (CD).The age of onset for many patients with UC and CD is between 15 and 30 years, with a second peak between 50 and 80 years of age. Aims: We aim to determine if there are differences in disease characteristics, outcomes, and IBD-related health care utilization between elderly patients with IBD diagnosed at a young age compared to those diagnosed later in life. Methods: A retrospective chart review of elderly (age ≥ 60 years) patients with IBD was conducted.Patients aged ≥ 60 years who were seen at the Saskatchewan Multidisciplinary IBD Clinic at the Royal University Hospital from 2012 to 2020 were included. Information on demographics, disease characteristics, and access to IBD-related health care was collected. Patients were divided in two groups according to age of diagnosis: <60 and ≥ 60 years. Chi-squares were used to compare the groups. Charts with missing data were omitted in the final analysis. Three patients with indeterminant colitis were excluded from the analyses. Logistic regression models were built to obtain odds ratios (OR) with their corresponding 95% confidence intervals (95%CI) and considering potential confounders. Results: In total, 264 patients were included in the study; 210(79.5%) diagnosed <60 and 54(20.5%) ≥ 60. The mean age of diagnosis was 47.21(SD=16.18), [<60=41.69(SD=13.25), ≥60=68.00(SD=6.264)].Cross tabulation (Table 2) of age of diagnosis and patient's characteristics (sex, IBD type, and clinical remission at last visit, current use of biologics and steroids) confirmed lack of inter-variable significance. However, in the same analysis individuals diagnosed ≥ 60 were more likely to be on 5-ASA therapy compared to their counterparts diagnosed before the age of 60. Logistic regression model results demonstrated that: Patients diagnosed ≥ 60 years were 2.06 (1.12–3.80, 95% CI) times more likely to be using 5-ASA therapy.Patients in clinical remission were 3.04 (95% CI, 1.65–5.61) times more likely to be using biologic therapy. Conclusions: Thus far, the results indicate significant correlation between use of 5-ASA in patients diagnosed age ≥60. In the same cohort, clinical remission was also linked to current use of biologics agents. On further analysis, with data stratification based on type of IBD, the same significance did not hold true, likely associated with low power within the stratified group. Clinical remission with those diagnosed ≥60 years while on biologics treatment, may reflect the specific disease type and inflammatory pathways responsible for second wave of IBD diagnosis in later ages.Patients diagnosed later in life were less likely to have IBD-related hospitalization or surgery, likely a reflection of shorted disease history. Funding Agencies: NoneNone